Progress in cassava breeding at the Chinese Academy of Tropical and Agric. Sciences (CATAS) - Lin, Xiong; Li, Kaimian; Zhang, Weite; Juang, Jie (International Center for Tropical Agriculture, 1998)
During the past 16 years the Chinese Academy of Tropical and Agricultural Sciences (CATAS) has made good progress in developing improved cassava varieties for China. Several improved varieties have been released in south China, of which cv. SC124, with high yield and good cold resistance, is already being planted on a large scale, mainly in Guangxi and Yunnan provinces. SC8002, which is characterized by a high yield potential and tolerance to cold, has mainly been released in Guangdong province, while SC8013, with high yield and good wind resistance, is being multiplied for planting in the typhoon affected areas of Hainan and Zhanjiang district of Guangdong. The release of these new varieties will improve the present situation of dependence on only two varieties, and will promote varietal comparisons, as well as stimulate the development of cassava production in China.